Narrative Analysis: Demonstrating the Iterative Process for New Researchers - Bright, Charmaine; Du Preez, Elizabeth (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2023)
This article demonstrates and describes an iterative process of narrative analysis for researchers who want to familiarise themselves with this methodology. The method draws on the six-step process of how to analyse a narrative, the four modes of reading a narrative and the three-sphere model of external context. The application of the method is demonstrated through describing the process of analysis of New Zealand school counsellors’ narratives of strengths-based counselling. Furthermore, this article posits that committing to a narrative analysis process of repeated and in-depth engagement with participants’ narrative data may facilitate a more robust and engaging research outcome than may otherwise have been achieved through more prescriptive methods of narrative analysis. Finally, this article highlights the use of story-map grids (tables) and models as visual aids to assist in the process of narrative analysis.